Frequency of interior knee joint pain after interlocking intermedullary nailing for fracture tibia shaft - Shaukat Hayat Khan; Muhammad Shahbaz Raza; Iffat Ara; Rehan Wani; Khalid Mehmood (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE:Tibial shaft fracture treatment with intermedullary nailing is very common these days. In the current study, our objective was to determine the percentage of patients with anterior knee pain following tibial shaft fracture treatment with interlocking intermedullary nailing. METHODOLOGY:Our research design was a Descriptive cross-sectional study. The study duration was approximately one year (03-3-2020 to 3-3-2021). The study was conducted at the orthopedics department of CMH Muzafarrabad. A sample of 125 participants was calculated. All patients underwent interlocking intermedullary nailing. We analyzed data using SPSS version 24. p-value less than 0.05 was considered statistically significant for result authenticity. RESULTS:In the present study 125 patients were included.Mean age of patients was 42.4±8.6SD years.Among all the patients, 82(65.6%) reported no pain while 43(34.4%) reported pain. Visual analogue scale showed mean pain scores 3.22±2.5SD and lysholm scores were 80.74±3.28SD (p≤0.000 and p≤0.000, respectively). CONCLUSION:Tibial shaft fractures are common these days. A relatively high incidence of anterior knee pain following intermedually nailing after tibial shaft fracture was found in our study.